Fecal microbiota transplant in patients with Clostridium difficile infection: A systematic review. Issue 4 (October 2016) - Chapman, Brandon C.; Moore, Hunter B.; Overbey, Douglas M.; Morton, Alex P.; Harnke, Ben; Gerich, Mark E.; Vogel, Jon D.
Abstract : BACKGROUND: Fecal microbiota transplantation (FMT) restores a diverse bacterial profile to the gastrointestinal tract and may effectively treat patients with Clostridium difficile infection (CDI). The objective of this systematic review was to evaluate the effectiveness of FMT in the treatment of CDI. METHODS: Ovid MEDLINE, EMBASE, Web of Science, and Cochrane database were used. The authors searched studies with 10 or more patients examining the resolution of symptoms after FMT in patients with CDI. Reviews, letters to the editors, and abstracts were excluded. Participants were patients with CDI. Intervention used was FMT. Quality assessment was performed using the Cochrane risk of bias assessment tool. Results were synthesized using a narrative approach. RESULTS: Retrospective and uncontrolled prospective cohort studies suggest that FMT is a highly effective therapy for recurrent/refractory CDI, with clinical success rates ranging from 83% to 100%, which is similar to rates published by two randomized controlled trials. Fecal microbiota transplantation may be effectively administered via antegrade (upper gastrointestinal) or retrograde (lower gastrointestinal) routes of delivery. Fecal microbiota transplantation rarely results in major adverse events. However, diarrhea, cramping, and bloating commonly occur and are typically self-limited. Most studies were uncontrolled retrospective studies. CONCLUSION: Fecal microbiota transplantation should be considered in patients with recurrent episodes of mild to moderate CDI who have failed conventional antimicrobial therapy. There is insufficient evidence to recommend FMT for the treatment of severe CDI. LEVEL OF EVIDENCE: Systematic review, level III.